ICT readiness and information security policies in OIC Countries - Abd Hadi, Nurafiqah Hanis; Zeki, Akram M. (IJSRP.ORG, 2016)
Information security is a priority for organization, businesses and even for the government. ICT readiness in all countries especially OIC countries are gradually increased and keep improving their technologies in fulfilling citizen needs. However, the level of ICT security and policies might be differ from each countries especially Muslim developed countries. Therefore, in this paper we are examine ICT development after 15 years, difference review on ICT development from Social Economic Research and Training Centre for Islamic Countries (SESRIC) and ICT Development Index (IDI) analysis from International Telecommunication Union (ITU) as well as the list of Information Security policies or laws that available in Bahrain, United Arab Emirates (UAE) and Saudi Arabia. And then we will explore a possible solution to deal with the associated ICT readiness and policies.